От жжизни к жизни: [сборник] / Евгений Гришковец - Гришковец Евгений (Махаон, 2012)
Экземпляры: АБ (20121120) / Инвентарный номер: 41191zzzzz / Цена: 288.53 / Сис.шифр: 84(2) / Авт.знак: Г 85 / ГРНТИ: 17.82.94 / ББК: 84(2=Рус)